X-threads as a Learning Stimulus for Universitary Students - Ayestarán Crespo, Raquel; Lavilla Muñoz, David José; Vega de la Faya, Oscar Roque (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
The article sheds light on how undergraduates in Marketing-related careers deepen their knowledge through the threads of the social network "X" (formerly Twitter). By reading existing documentation and conducting student surveys, information is obtained on whether they represent a stimulus to deepen learning or are limited to being informative pills that begin and end in themselves, not motivating the student to further research. The results offer a critical view of their role in the learning process, identifying the imprint they leave on students.